Preeruptive intracoronal resorption: a review of the literature - Pérez Lip, Iván Eduardo (2023)
Preeruptive intracoronal resorption (PIRR) is a radiographic phenomenon characterized by the presence of a radiolucent area situated in the coronal dentin near the amelodentine junction within the tooth's germ. Typically, this radiolucent area is singular and shallow, encompassing less than one-third of the chambered dentin. The reported frequency in the literature varies between 0.85% and 27.3%. No association with gender has been identified, and it predominantly affects posterior teeth. While its precise etiology remains undetermined, histological evidence suggests that it results from a sequelae of dentin resorption. RIPE Defects as Caries Lesions: Once the tooth erupts into the oral cavity, RIPE defects should be regarded in a manner similar to caries lesions. Despite the absence of established treatment schemes or clinical practice guidelines, reported treatments are contingent upon the depth of the defects and frequently lean towards conservative approaches. The primary aim of this study was to comprehensively review descriptive studies and published case reports focusing on RIPE defects. This effort is directed towards integrating these defects into routine clinical practice considerations.